Resistência à insulina na Neurofibromatose tipo 1 - Aline Stangherlin Martins (2017)
Introduction: Data suggests a lower occurrence of diabetes mellitus (DM) in patients with neurofibromatosis type 1 (NF1). The type 2 diabetes mellitus (DM2) is the form present in about 90% of cases of DM and it is associated with insulin resistance (IR). Objective: To evaluate metabolic and nutritional characteristics related to IR in individuals with NF1compared to individuals without the disease. Methods: This study was realized in two phases. In phase one, we study the fasting blood glucose levels (FBG) in individuals with NF1 from the Neurofibromatosis Outpatient Reference Center of Federal University of Minas Gerais(CRNF-UFMG) by through a review of medical records. The weight, height and FBG levels data were recorded. The FBG levels of individuals with NF1 was compared to a sample of participants in the Study of Adult Health Longitudinal (ELSA) matched by sex, age and body mass index (BMI), in the proportion of one case for each three controls. In phase two, we selected individuals with NF1 from the CRNF-UFMG matched by sex, age and BMI with controls from the community. The participants underwent anamnesis, dietary and nutritional assessment and collection of blood samples for evaluation of glycemic profile, insulin, glycated hemoglobin, lipid profile and adipocytokines. The indicators Homeostasis Model Assessment Insulin Resistance (HOMA-IR), Homeostasis Model Assessment Beta Cell Function (HOMA-Beta); Homeostasis Model Assessment Adiponectin (HOMA-AD), Quantitative insulin sensitivity index (QUICKI), and Adiponectin/Leptin ratio (ALR) wereused to determine IR. Results: In the phase 1, were included 57 medical records of individuals with NF1 and 171 ELSA controls. The results showed a lower median of FBG (NF1: 86.0 mg/dL (81.0 to 95.5); controls: 102.0 mg/dL (96.0 108.0), p < 0.001) and a lower prevalence (NF1: 16%; controls: 63%, p < 0.001) as well as lower chance (OR: 0.11;95% CI: 0.07 to 0.19) of developing high FBG levels in the NF1 group. In phase 2, were evaluated 40 individuals with NF1 and 40 controls. HOMA-AD was significantly lower in the NF1 group (NF1: 1.0 (0.5 1.7); control: 1.9 (1.0 4.1), p = 0.003). ALR was significantly higher in the NF1 group (NF1: 3.8 (2.1 12.6); controls: 1.2 (0.7 2.1), p = 0.003). Nodifferences were observed between the groups in relation to HOMA-IR, HOMA-Beta and QUICKI. About nutritional characteristics, weight (NF1: 60.8 ± 13.1 kg, controls: 68.6 ± 14.5 kg, p < 0.001), height (NF1: 1.57 m (1.51 1.63), controls: 1.62 m (1.57 1.74), p < 0.001), fat free mass (NF:43.7 ± 7.9 kg, controls: 47.2 ± 9, p < 0.001), p = 0.036), fat percentage(NF1: 26.9 ± 8.1 kg, controls: 30.6 ± 7.3 kg, p = 0.015), fat mass (NF1: 16.9 ± 7.5 kg; controls: 21,3 ± 8,1 kg, p = 0,036) and body water (NF1: 31.4 ± 6.1, controls: 34.1 ± 7.4 L, p < 0.001) were significantly lower in NF1 group. In relation to the metabolic characteristics, the FBG levels of NF1 subjects was significantly lower than the controls (NF1: 83.5 mg/dL(78.0 90.0), control: 86.0 mg/dL (83.0 94.0), p = 0.008). Adiponectin levels were significantly higher (NF1: 23.7 g/mL (17.0 39.4); controls: 15.0 g/mL (11.3 20.9), p < 0.001) and visfatin levels (NF1: 118.2 ng/mL (105.8 124.8), controls: 138.2 ng/mL (125.5 147.7), p = 0.001) were significantly lower in subjects with NF1. No significant differences were observed in blood glucose levels two hours after 75 g of dextrosol, insulin, glycated hemoglobin, leptin and resistin. HOMA-AD showed a significant correlation with other markers of IR (HOMA-IR, HOMA-Beta, QUICKI and ALR), with nutritional characteristics (BMI, waist circumference, waist/height ratio, fat mass and fat free mass), withthe DM indicators (FBG, glycemia post-dextrosol and glycated hemoglobin), with serum lipids (VLDL and triglycerides) and adipocytokines (adiponectin, leptin, visfatin). AL presented inverse correlation with fat mass, BMI, leptin, visfatin and direct correlation withadiponectin. According to the multiple linear regression model, the triglycerides, fat mass and visfatin significantly influenced HOMA-AD and FBG, visfatin, fat mass and waist circumference significantly influenced RAL. Conclusion: The results of this study suggests that lower fat mass, FBG, visfatin and HOMA-AD levels and higher adiponectin levels andALR may be related to a high insulin sensitivity and lower occurrence of DM2 in NF1 individuals.